The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s13071-018-2645-7
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of apicomplexan parasites infecting commercially valuable species from the North-East Atlantic reveals high levels of diversity and insights into the evolution of the group

Abstract: BackgroundThe Apicomplexa from aquatic environments are understudied relative to their terrestrial counterparts, and the seminal work assessing the phylogenetic relations of fish-infecting lineages is mostly based on freshwater hosts. The taxonomic uncertainty of some apicomplexan groups, such as the coccidia, is high and many genera were recently shown to be paraphyletic, questioning the value of strict morphological and ecological traits for parasite classification. Here, we surveyed the genetic diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 49 publications
2
19
0
5
Order By: Relevance
“…A novel Apicomplexa, parasitic alveolate specific to the Scomber japonicus fish species was discovered which had a high prevalence in all body sites, particularly the gill and pyloric ceca. Relatively little is known about the genetics and evolution of Apicomplexa parasites, but several coccidia, including Eimeria , Goussia , and Calyptospora , have been recently identified in various species of commercially important marine fish ( 24 ). Lastly, an important fish pathogen, Photobacterium damselae , was observed in high prevalence on GI, skin, and digesta communities and was associated with the summer months, which exhibit higher temperatures and low nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…A novel Apicomplexa, parasitic alveolate specific to the Scomber japonicus fish species was discovered which had a high prevalence in all body sites, particularly the gill and pyloric ceca. Relatively little is known about the genetics and evolution of Apicomplexa parasites, but several coccidia, including Eimeria , Goussia , and Calyptospora , have been recently identified in various species of commercially important marine fish ( 24 ). Lastly, an important fish pathogen, Photobacterium damselae , was observed in high prevalence on GI, skin, and digesta communities and was associated with the summer months, which exhibit higher temperatures and low nutrients.…”
Section: Discussionmentioning
confidence: 99%
“…The Haemohormidium -like parasite was basal to a major monophyletic clade containing species of coccidia, a finding comparable to that of Renoux et al (2017) . Furthermore, amplicons retrieved in this study and in Renoux et al (2017) formed a monophyletic clade with that of apicomplexans of unknown identity retrieved during a molecular survey from tissues of the liver of Solea senegalensis ( MF468328 ) and the heart of Pagrus caeruleostictus ( MF468323 ), both species of fish collected from the Northeast Atlantic (see Xavier et al, 2018 ).
Fig.
…”
Section: Resultsmentioning
confidence: 63%
“…For the phylogenetic analysis sequences generated of the Haemohormidium -like parasite from the different species of damselfish and from the different sites were compared. Comparative sequences of coccidia (with reference to the findings of Renoux et al, 2017 ) with Adelina dimidiata (GenBank: DQ096835 ) as outgroup (following Barta et al, 2012 ; Xavier et al, 2018 ), were downloaded from GenBank and aligned to the sequences generated within this study. Sequences were aligned using the Clustal W alignment tool ( Thompson et al, 1994 ) implemented in Geneious Ver.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SSR rDNA‐based phylogeny obtained in the present study returned an arrangement similar to that found in previous studies, with the clade composed by species of the genus Goussia and Eimeria with marked polyphyletic (Jirku et al, ; Xavier et al, ). The findings of the Bayesian inference, together with the divergences observed in the morphology of the oocysts and sporocysts of Goussia guamaensis n. sp.…”
Section: Discussionmentioning
confidence: 99%